HABITAT OPTIMAL GAJAH SUMATERA (Elephas maximus sumatranus Temminck.) DI PUSAT LATIHAN GAJAH (PLG) MINAS - Nur Suhada; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Sumatran Elephant (Elephas maximus sumatranusTemminck.) is the one of animals was endangered and the largest animal that still alive and could be only found on the Sumatera Island. The aim of this research was identified optimal habitat sumatran elephant in the training centre of elephant (PLG) Minas and to knews suitability between sumatran elephant habitat at the training centre of elephant (PLG) Minas with criteria habitat in the nature. Data observation and direct observation in location and interview were conducted during the research arranged into the table. Data that could not displayed in the table were be treated descriptively. The needs of elephant in the nature are influencedby shelter availability, food availability,water availability, mineral salt, home range and security comfort. Result of this research can be concluded that there it has been obtained habitat optimal sumatran elephant in the training centre of elephant (PLG) Minas is : shelter, water, mineral salt and security comfort. The suitability habitat in the training centre of elephant (PLG) Minas with criteria of natureis : shelter, water, mineral salt and security comfort, while unsuitability is : food and home range. Keyword : Sumatran elephant, habitat, the training centre of elephant (PLG) Minas